Factors Affecting Repurchase Intention - Novita, Wanda; Toar, Yandri Ardolof (Jurnal Informatika Ekonomi Bisnis, 2024)
This research endeavors to scrutinize the determinants influencing consumers' satisfaction for repurchasing intention on the Shopee platform, with customer satisfaction posited as an intermediary variable. Employing a quantitative methodology, data from respondents were collected through a google form survey. The sampling strategy involved convenience sampling, yielding a cohort of 102 participants. Data analysis was executed using a partial least squares structural equation model (PLS-SEM), validated through SmartPls 3.0. The findings indicated that delivery service, brand reputation, and cashback promotions exerted a favorable impact on customer satisfaction, thereby positively influencing repurchase intentions. Moreover, customer satisfaction emerged as a mediating factor in the correlation between service delivery and repurchase intentions, as well as between cashback promotions and repurchase intentions.